A Clinical Decision Rule Identifies Risk Factors Associated With Antimicrobial-Resistant Urinary Pathogens in the Emergency Department: A Retrospective Validation Study. (June 2015) - Faine, Brett A.; Harland, Kari K.; Porter, Blake; Liang, Stephen Y.; Mohr, Nicholas
Background: Identifying patients at high risk for multidrug-resistant urinary tract infections (UTIs) is important for guiding empirical antimicrobial therapy. Clinical risk factors associated with antimicrobial-resistant urinary pathogens and the derivation of a simple clinical decision rule could help define health care–associated UTI.Objective: To derive a simple clinical decision rule to identify clinical risk factors associated with antimicrobial-resistant urinary pathogens.Methods: This was a retrospective case-control study of all emergency department (ED) patients from July 1, 2011, to July 1, 2012, who presented to the ED with UTI and a positive urine culture. Candidate risk factors were collected retrospectively from medical record review. We compared differences in patient characteristics stratified by the presence of an antimicrobial-resistant urinary pathogen.Results: A total of 360 patients with UTI had a positive, noncontaminated urine culture during the study period. About 6.7% of patients (n = 24) had a multidrug-resistant (MDR) urinary infection. Logistic regression modeling identified 3 clinical factors associated with the identification of a MDR pathogen: male sex, chronic hemodialysis, and nursing home residence. A scoring system was created to identify patients with MDR pathogens. Test characteristics were calculated using bootstrapping for internal validation, with a sensitivity of 74.7% (95% CI = 55.1%-91.3%) and specificity of 85.1% (95% CI = 77.8%-86.2%), positive likelihood ratio of 4.3, and a negative likelihood ratio of 0.3.Conclusions: Clinical factors can be used to identify UTI patients at high risk of MDR urinary pathogens.